Necessary and sufficient conditions for complementary stochastic quadratic operators of finite-dimensional simplex - Abdulghafor, Rawad; Turaev, Sherzod; Zeki, Akram M. (Sukkur IBA, 2017)
We define a complementary stochastic quadratic operator on ﬁnite-dimensional space as a new sub-class of quadratic stochastic operator. We give necessary and sufficient conditions for complementary stochastic quadratic operator.